Peran Mediasi Kepuasan Pelanggan pada Hubungan Social Media Marketing dan Kualitas Produk terhadap Niat Beli Ulang - Abiyu Syahreza, Dafa; Evanita, Susi (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study aims to comprehensively analyze the influence of social media marketing and product quality on repurchase intention, with customer satisfaction as a mediating variable, among consumers of Magenta’s creative food products in Padang City. The research is motivated by the importance of leveraging social media as an effective promotional tool and maintaining consistent product quality to sustain and enhance customer loyalty. A quantitative research approach was employed using a survey method, involving 100 respondents who are active Magenta consumers. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the relationships between variables simultaneously. The findings reveal that social media marketing and product quality have a positive and significant effect on customer satisfaction. Furthermore, both variables also positively and significantly influence repurchase intention, both directly and indirectly through the mediating role of customer satisfaction. These results underscore that effective social media marketing strategies, combined with improved product quality, play a crucial role in fostering customer satisfaction, which in turn drives sustainable repurchase intentions